2021
DOI: 10.1002/jgm.3320
|View full text |Cite
|
Sign up to set email alerts
|

Circulating status of microRNAs 660‐5p and 210‐3p in breast cancer patients

Abstract: Background MicroRNAs (miRs), which are stable in the blood, comprise small non‐coding RNAs that regulate gene expression. They have important roles in almost all biological pathways, especially in cancer‐relevant processes, and have an abnormal expression in breast cancer. In recent studies, the aberrant expression level of various microRNAs has been demonstrated in human cancer. In the present study, the status of serum microRNA‐210‐3p and microRNA‐660‐5p expression levels in breast cancer patients was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…miR - 660 was upregulated in breast and liver cancer [ 25 , 26 , 27 , 28 ]. miR - 660 had low expression in lung cancer and targeted MDM2, which induced destabilization of the p53 protein, thus promoting cell proliferation in lung cancer [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR - 660 was upregulated in breast and liver cancer [ 25 , 26 , 27 , 28 ]. miR - 660 had low expression in lung cancer and targeted MDM2, which induced destabilization of the p53 protein, thus promoting cell proliferation in lung cancer [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current study was conducted on all the patients referred to the affiliated hospitals of Babol University of Medical Sciences, Babol, Iran, within May 2016 to February 2017. There was a previous report on the status of miRNAs in the aforementioned samples (23,24).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, miR-210 targets the EFNA3 gene which makes it pro-angiogenic miRNA in BC tumorigenesis ( 54 ). Besides, a number of studies also demonstrate that the circulating levels of miR-210 are increased in BC patients ( 89 , 138 , 160 ). Qattan et al.…”
Section: Diagnostic and Prognostic Function Of Mirnas In Breast Cancermentioning
confidence: 99%
“…Interestingly, miR-210 targets the EFNA3 gene which makes it pro-angiogenic miRNA in BC tumorigenesis (54). Besides, a number of studies also demonstrate that the circulating levels of miR-210 are increased in BC patients (89,138,160). Qattan et al have revealed that the significantly augmented levels of miR-210-3p which is implicated in certain signaling pathways are specific to the TNBC subtype of BC (138).…”
Section: Mir-210mentioning
confidence: 99%